A-019 unexpectedly high cardiac troponin values in healthy athletes after SARS-CoV-2 infection - Hammerer-Lercher, A.; Kissel, C.; Wittfooth, S.; Huré, G.; Sanzone, A.; Neyer, P.; Bernasconi, L.; Manka, R.; Noack, P.; Hof, D.; Hammarsten, O.; Mueller, C. (Clinical Chemistry, 2024)
Background Elevated levels of cardiac troponin I or T (cTnI, cTnT) in general have immediate clinical consequences including invasive cardiac imaging and rhythm monitoring. Macro-troponin is a complex of antitroponin autoantibodies and cTnI or cTnT and may result in falsely elevated values. In athletes, a reliable exclusion of cardiac disease is crucial to allow for intensive exercise. The prevalence and causes of falsely elevated cTn in professional athletes after SARS-CoV-2 infection are unknown.